2013
DOI: 10.1080/03075079.2011.643862
|View full text |Cite
|
Sign up to set email alerts
|

Carry-over effects in perceptions of educational value

Abstract: The marketisation of higher education has led to the need for universities to apply marketing concepts normally associated with commercial markets to the educational context. Consumer value, which considers how consumers perceive the outcomes of their consumption experiences, is one such concept. This study examines the impact that students' perceptions of educational value at a specific point in time have on subsequent evaluations of value during a one-year programme of study. Data were collected from a match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 95 publications
0
18
0
Order By: Relevance
“…In almost all cases, these perceptions became more positive as the applicability of the skills gained, and status afforded by the doctorate, became more apparent. Changes in perceptions of educational value in undergraduate study have been identified (Kalafatis & Ledden, 2013), but our results are the first to suggest an increase in perceived doctoral value over time.…”
Section: Research Question 2 -Factors Influencing Doctoral Valuementioning
confidence: 59%
See 2 more Smart Citations
“…In almost all cases, these perceptions became more positive as the applicability of the skills gained, and status afforded by the doctorate, became more apparent. Changes in perceptions of educational value in undergraduate study have been identified (Kalafatis & Ledden, 2013), but our results are the first to suggest an increase in perceived doctoral value over time.…”
Section: Research Question 2 -Factors Influencing Doctoral Valuementioning
confidence: 59%
“…Postgraduates in HE may experience changing value perceptions affected by social and cultural factors, in addition to economic reward (Kalafatis & Ledden, 2013). Despite much media commentary on the subject, very little research explores the contextual factors of personal, social, and cultural value that individuals derive from the doctorate (Raddon & Sung, 2009), and the intellectual perspectives they develop (Boulos, 2016;Pitt, 2008).…”
Section: Concepts Of Value In Doctoral Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…While the international perception over the last century has been that the United States' culture of innovation and its university system's emphasis on private-public partnership has created the best higher education system in the world, this perception is changing [8]. Perceptions of quality and value are not static and are highly influenced by changes in stakeholder perceptions of success, shifts regarding competitive forces within markets, and new social attitudes [3,[9][10][11][12][13][14][15][16][17][18][19][20][21][22]. For example, while conceptions of "quality" and "value" in the service industry are based upon previous experience, personal expectations, and institutional image, in higher education, they may derive from institutional reputation, esteem of research, the volume of work published, and postgraduate employability rates [23].…”
Section: International Educationmentioning
confidence: 99%
“…2. Use of both formative construct and reflective variables (Kalafatis & Ledden, 2013). CSR practices are modeled as a formative variable, 2nd order-factor including 6 aspects forming at lower level form and financial performance is also a formative variable, 2nd order-factor consists of 2 aspects forming at lower level.…”
Section: Analysis Methodsmentioning
confidence: 99%